Rapid Detection and Characterization of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Omicron Variant in a Returning Traveler - Sexton, Mary Elizabeth; Waggoner, Jesse J; Carmola, Ludy R; Nguyen, Phuong Vi; Wang, Ethan; Khosravi, Dara; Taz, Azmain; Arthur, Robert A; Patel, Mit; Edara, Venkata Viswanadh; Foster, Stephanie L; Moore, Kathryn M; et al. (Clinical infectious diseases, 2022)
Abstract We describe rapid detection of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant using targeted spike single-nucleotide polymorphism polymerase chain reaction and viral genome sequencing. This case occurred in a fully vaccinated and boosted returning traveler with mild symptoms who was identified through community surveillance rather than clinical care.